Chemical constituents of Artocarpus kemando (Moraceae). - Ee, Gwendoline Cheng Lian; Bong, Joseph Choon Fah; Rahmani, Mawardi; Teo, Siow Hwa; Lim, Che Kiong (Chemical Publishing Co., 2011)
The stem bark of Artocarpus kemando furnished 24-methylenecycloartenyl acetate (fatty acyl ester) (1) together with cycloartobiloxanthone (2). Compound 1 was obtained for the first time from this species. Structures of both compounds were determined using NMR and MS analysis. A cytotoxic study showed that the crude extract of the stem bark of Artocarpus kemando was significantly active against the HL-60 (human promyelocytic leukemia cell) and IMR-32 (human neuroblastoma cell) cell lines. This is the first report on the cyctotoxic activity of Artocarpus kemando. Dynamic Metadata(s).